WW domain interactions regulate the Hippo tumor suppressor pathway - Salah, Z (Nature Publishing Group, 2011)
The Hippo kinase pathway is emerging as a conserved signaling pathway that is essential for organ growth and tumorigenesis in Drosophila and mammalians. Although the signaling of the core kinases is relatively well understood, less is known about the upstream inputs, downstream outputs and regulation of the whole cascade. Enrichment of the Hippo pathway components with WW domains and their cognate proline-rich interacting motifs provides a versatile platform for further understanding the mechanisms that regulate organ growth and tumorigenesis. Here, we review recently discovered mechanisms of WW domain-mediated interactions that contribute to the regulation of the Hippo signaling pathway in tumorigenesis. We further discuss new insights and future directions on the emerging role of such regulation.